Distribution of prostate cancer recurrences on gallium‐68 prostate‐specific membrane antigen (68Ga‐PSMA) positron‐emission/computed tomography after radical prostatectomy with pathological node‐positive extended lymph node dissection. (23rd April 2020) - Huits, Thijs H.; Luiting, Henk B.; van der Poel, Henk G.; Nandurkar, Rohan; Donswijk, Maarten; Schaake, Eva; Vogel, Wouter; Roobol, Monique J.; Wit, Esther; Stricker, Phillip; Emmett, Louise; van Leeuwen, Pim J.
Abstract : Objectives: To examine the anatomical distribution of prostate cancer (PCa) recurrence on gallium‐68 prostate‐specific membrane antigen ( 68 Ga‐PSMA) positron‐emission tomography (PET)/computed tomography (CT) in patients with biochemical recurrence (BCR) after undergoing radical prostatectomy (RP) with pathological lymph node metastasis (pN1) in their extended pelvic lymph node dissection (ePLND), and to compare the location of PCa recurrence with the location of the initial lymph node metastasis at ePLND. Materials and Methods: We retrospectively reviewed 100 patients with BCR (PSA 0.05–5.00 ng/mL) after RP with pN1 ePLND who underwent 68 Ga‐PSMA PET/CT to guide salvage therapy. Clinical and pathological features and anatomical locations of PCa recurrence on 68 Ga‐PSMA PET/CT were obtained, and management impact was recorded. Results: In all, 68 patients (68%) had a positive and 32 patients (32%) had a negative 68 Ga‐PSMA PET/CT result. Of the 68 patients with a positive 68 Ga‐PSMA PET/CT, 44 (65%) showed abnormal uptake only in the pelvic area, seven (10%) only outside the pelvic area, and 17 (25%) both within and outside the pelvic area. 68 Ga‐PSMA PET/CT‐positive pelvic lymph nodes were often (84%) detected on the same side as the lymph node metastasis diagnosed at ePLND. Based on the outcomes of the 68 Ga‐PSMA PET/CT, change of management was noted in 68% of the patients. Conclusion: Recurrence of PCa on 68 Ga‐PSMA PET/CT was limited to the pelvis in the majority of patients with BCR after RP with pN1 ePLND. Moreover, recurrence was often detected on the same side as the lymph node metastasis at ePLND. The results confirm the diagnostic value of 68 Ga‐PSMA PET/CT in patients with BCR after RP with pN1 ePLND. Prospective studies are needed to support the long‐term benefit of 68 Ga‐PSMA PET/CT‐dictated management changes.